1994
DOI: 10.1183/09031936.94.07030477
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in smoking effects on adult pulmonary function

Abstract: Data on 1,618 male and 1,669 female adults aged 40-69 yrs, from China in the Beijing Respiratory Health Study, were analysed to investigate the gender differences in effects of smoking on pulmonary function. Smoking was characterized by total smoking-years, smoking status (former, transitional and constant), smoking type (cigarette, cigar and others). The effects of smoking on height-standardized forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) were assessed by multiple regressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
72
2
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 11 publications
18
72
2
6
Order By: Relevance
“…These findings are in line with several studies indicating an increased susceptibility to tobacco smoke among women. 26,27 However, in our study, the stronger effect of smoking in women on sputum production and recurrent wheeze seemed to be explained by women starting earlier and smoking more.…”
Section: Table 2 Association Between Different Independent Variablescontrasting
confidence: 47%
See 1 more Smart Citation
“…These findings are in line with several studies indicating an increased susceptibility to tobacco smoke among women. 26,27 However, in our study, the stronger effect of smoking in women on sputum production and recurrent wheeze seemed to be explained by women starting earlier and smoking more.…”
Section: Table 2 Association Between Different Independent Variablescontrasting
confidence: 47%
“…1 In 2012, even higher figures were reported from the Stockholm high schools where 37% of 17-year-old girls and 29% of boys smoked regularly. 2 Similarly, recent national Swedish statistics show that the general trend of decreased smoking in the population is no longer present in young women aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29] years, where daily smoking increased from 10% in 2009 to 13% in 2011. 3 Smoking rates have traditionally been higher in men, but women are increasingly starting to smoke at an age equivalent to that of men.…”
Section: Introductionmentioning
confidence: 99%
“…These results include negative effect on lung growth [1], lower lung function in adulthood [2], increased bronchial responsiveness [3], higher rate of hospitalisation for chronic obstructive pulmonary disease [4], and higher risk of respiratory symptoms [5]. There are, however, conflicting reports on sex differences for the negative effect on lung function of tobacco smoking [2,6]. Even if there are sexrelated differences in perception, reporting and interpretation of respiratory symptoms and diseases [7], a symptom like shortness of breath is found to be associated with quality of life and to predict mortality equally well in both sexes [8].…”
mentioning
confidence: 99%
“…Several epidemiological studies of cigarette smoke have shown that, at the same exposure level, women differ in their resistance to lung damage compared to men. Xu et al (94) report that adverse effects of smoking on pulmonary function are greater in women than in men, and other studies indicate sex differences in lung dysfunction, and in genetic and biochemical alterations in lung cancer (95)(96)(97).…”
Section: Analysis Of Variability and Susceptibilitymentioning
confidence: 99%